Peranan Pengawas Dalam Meningkatkan Mutu Pendidikan Pada Sekolah Dasar Negeri di Kecamatan Bataguh Kabupaten Kapuas - R Rusiana; I Irawanto (Administraus, 2019)
This study discusses how the role of supervisors in improving the quality of education in public elementary schools in Bataguh District, Kapuas Regency, a description of the implementation of the duties of school supervisors in state elementary school education units, and what are the supporting and inhibiting factors of the role of school supervisors in improving the quality of education in public elementary schools (SDN) in Bataguh District, Kapuas Regency. This type of research is a qualitative descriptive study with a research location at the Education Unit of the Bataguh, Kapuas Regency. Data collection techniques used in this study were interviews, observation, and documentation. The informant in this study was the school supervisor of the Elementary School (SDN) education unit in Bataguh Subdistrict of Kapuas Regency with a total of 4 people with 34 target schools. As for the key informants in this study were the Coordinator of the Supervisor (Korwas) and the Head of the Education Unit of the Bataguh Sub-District of Kapuas Regency. Based on the results of the study it is known that: 1) The implementation of the duties of school supervisors in the State Elementary School education unit in Bataguh Subdistrict of Kapuas Regency has been carried out well, namely: Planning and preparing supervisory devices before conducting supervision with the existence of annual programs, monthly programs and assessment instruments; Implement the supervision program in the target schools by identifying schools and teachers who will be supervised through a questionnaire and formulating the factors influencing the smoothness of supervision through the formulation of supervision programs; the supervision techniques used are mostly individual; and follow up on supervision results in the form of quantitative and qualitative assessments and reports; 2) The role of school supervisors in improving the quality of education in public elementary schools in Bataguh District, Kapuas Regency, including: the role of school supervisors in supervising/inspecting; as advising giving advice/motivation; as supervisor/monitoring; as reporting (making report); coordinate/coordinating; and performing leadership/leading and implementing. 3) Supporting factors for the role of school supervisors in improving the quality of education include: support from the government in the form of official motorcycles; additional operational allowances from the Regional Government; place of domicile; the enthusiasm of the education supervisor; training in competency improvement; students; teachers and facilities / infrastructure in schools. The inhibiting factors include geographical location; road access; mastery of science and technology; and lack of educational school supervisory resources with a large number of target schools. Penelitian ini membahas tentang bagaimana peranan pengawas dalam meningkatkan mutu pendidikan pada Sekolah Dasar Negeri di Kecamatan Bataguh Kabupaten Kapuas, gambaran pelaksanaan tugas pengawas sekolah satuan pendidikan Sekolah Dasar Negeri, serta apa saja faktor pendukung dan penghambat peranan pengawas sekolah dalam meningkatkan mutu pendidikan pada Sekolah Dasar Negeri (SDN) di Kecamatan Bataguh Kabupaten Kapuas Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan lokasi penelitian pada UPT Dinas Pendidikan Kecamatan Bataguh Kabupaten Kapuas. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi, dan dokumentasi. Informan dalam penelitian ini adalah pengawas sekolah satuan pendidikan Sekolah Dasar Negeri (SDN) di Kecamatan Bataguh Kabupaten Kapuas yang berjumlah 4 orang dengan jumlah sekolah binaan sebanyak 34 satuan pendidikan Sekolah Dasar. Adapun yang menjadi key informan dalam penelitian ini adalah Koordinator Pengawas (Korwas) serta Kepala UPT Dinas Pendidikan Kecamatan Bataguh Kabupaten Kapuas Berdasarkan hasil penelitian diketahui bahwa: 1) Pelaksanaan tugas pengawas sekolah satuan pendidikan Sekolah Dasar Negeri di Kecamatan Bataguh Kabupaten Kapuas telah terlaksana dengan baik yaitu: Merencanakan dan menyiapkan perangkat kepengawasan sebelum melakukan supervisi dengan adanya program tahunan, program bulanan dan instrumen penilaian; Melaksanakan program supervisi di sekolah binaan dengan mengidentifikasi sekolah dan guru-guru yang akan disupervisi melalui daftar isian dan merumuskan faktor-faktor mempengaruhi kelancaran supervisi melalui rumusan program supervisi; teknik supervisi yang dipergunakan yakni lebih banyak bersifat individual; dan tindak lanjut hasil supervisi dalam bentuk penilaian kuantitatif dan kualitatif serta laporan; 2) Peranan pengawas sekolah dalam meningkatkan mutu pendidikan pada Sekolah Dasar Negeri di Kecamatan Bataguh Kabupaten Kapuas, meliputi: peranan pen gawas sekolah dalam mensupervisi/ inspecting; sebagai advising memberikan nasehat/motivasi; pemantau/monitoring; sebagai reporting (membuat laporan); mengkoordinir/coordinating; dan performing leadership/memimpin dan melaksanakan. 3) Faktor pendukung peranan pengawas sekolah dalam meningkatkan mutu pendidikan meliputi: dukungan dari pemerintah berupa motor dinas; tunjangan tambahan operasional dari Pemerintah Daerah; tempat domisili; semangat kerja pengawas pendidikan; pelatihan dalam peningkatan kompetensi; siswa; guru dan sarana/ prasarana di sekolah. Adapun faktor penghambat meliputi letak geografis; akses jalan; penguasaan IT; dan kurangnya SDM pengawas sekolah pendidikan dengan jumlah sekolah binaan yang cukup banyak.